Tuning of the electronic and vibrational properties of epitaxial MoS2 through He-ion beam modification. (19th February 2023) - Parida, Shayani; Wang, Yongqiang; Zhao, Huan; Htoon, Han; Kucinski, Theresa Marie; Chubarov, Mikhail; Choudhury, Tanushree; Redwing, Joan Marie; Dongare, Avinash; Pettes, Michael Thompson
Abstract: Atomically thin transition metal dichalcogenides (TMDs), like MoS2 with high carrier mobilities and tunable electron dispersions, are unique active material candidates for next generation opto-electronic devices. Previous studies on ion irradiation show great potential applications when applied to two-dimensional (2D) materials, yet have been limited to micron size exfoliated flakes or smaller. To demonstrate the scalability of this method for industrial applications, we report the application of relatively low power (50 keV) 4 He + ion irradiation towards tuning the optoelectronic properties of an epitaxially grown continuous film of MoS2 at the wafer scale, and demonstrate that precise manipulation of atomistic defects can be achieved in TMD films using ion implanters. The effect of 4 He + ion fluence on the PL and Raman signatures of the irradiated film provides new insights into the type and concentration of defects formed in the MoS2 lattice, which are quantified through ion beam analysis. PL and Raman spectroscopy indicate that point defects are generated without causing disruption to the underlying lattice structure of the 2D films and hence, this technique can prove to be an effective way to achieve defect-mediated control over the opto-electronic properties of MoS2 and other 2D materials.